Impact of Modified Frozen Elephant Trunk Procedure on Downstream Aorta Remodeling in Acute Aortic Dissection: CT Scan Follow-Up - Koechlin, Luca; Kaufmann, Josefin; Macius, Evelina; Bremerich, Jens; Sommer, Gregor; Gahl, Brigitta; Schurr, Ulrich; Grapow, Martin; Reuthebuch, Oliver; Eckstein, Friedrich; Berdajs, Denis A. (World journal of surgery, 2020)
Objectives The aim was to evaluate the impact of a modified frozen elephant trunk procedure (mFET) on remodeling of the downstream aorta following acute aortic dissections. Methods Over a period of 8 years, 205 patients (mean age 62.6 ± 12.6 years) underwent a mFET ( n = 69, 33.7%) or isolated ascending aorta replacement ( n = 136, 66.3%) (iAoA). Aortic diameter was assessed at the aortic arch (AoA), at the mid of the thoracic aorta (mThA), at the thoracoabdominal transition (ThAbd) and at the celiac trunk level (AbdA). Results Mean follow-up was 3.3 ± 2.6 years. In-hospital mortality was 14% ( n = 28), 7% in mFET and 17% in the iAoA group ( p = 0.08). At the end of the follow-up, overall survival was 84% (95% CI 70–92%) and 75% (65–82%) and freedom from aorta-related reoperation was 100% and 95% (88–98%) for mFET and iAoA, respectively. At iAoA, the average difference in diameter change per year between mFET and iAoA was for total lumen 0 mm (− 0.95 to 0.94 mm, p = 0.99), and for true lumen, it was 1.23 mm (− 0.09 to 2.55 mm) per year, p = 0.067. False lumen demonstrated a decrease in diameter in mFET as compared to iAoA by − 1.43 mm (− 2.75 to − 0.11 mm), p = 0.034. In mFET, at the aortic arch level the total lumen diameter decreased from 30.7 ± 4.8 mm to 30.1 ± 2.5 mm (Δ r + 2.90 ± 3.64 mm) and in iAoA it increased from 31.8 ± 4.9 to 34.6 ± 5.9 mm (Δ r + 2.88 ± 4.18 mm). Conclusion The mFET procedure provides satisfactory clinical outcome at short term and mid-term and has a positive impact on aorta remodeling, especially at the level of the aortic arch.